A turn-on upconversion fluorescence sensor for acrylamide in potato chips based on fluorescence resonance energy transfer and thiol-ene Michael addition. (30th July 2021) - Rong, Yawen; Ali, Shujat; Ouyang, Qin; Wang, Li; Wang, Bing; Chen, Quansheng
Highlights: A novel method for the determination of acrylamide was developed. The sensor was based on FRET between UCNPs and RBD regulated by GSH. Acrylamide was sensing by thiol-ene Michael addition reaction between GSH and AA. The sensor has good results on the sensitivity and practicality for potato chips. Abstract: This study describes a turn-on upconversion fluorescence sensor for the detection of acrylamide (AA) based on glutathione (GSH) modulated turn-on fluorescence strategy. Polyethyleneimine-modified upconversion nanoparticles were first prepared by the hydrothermal method and then Rhodamine B derivative (RBD) was loaded on their surface through non-covalent bonding. The GSH coupled with RBD and strongly quenched the upconversion fluorescence via fluorescence resonance energy transfer. Upon addition of tris (2-carboxyethyl) phosphine, the thiol-ene Michael addition reaction between GSH and AA was efficiently catalyzed, resulted in the quenched fluorescence triggered on. Under the optimum conditions, a linear detection range from 0.1 to 10 4 μM was implemented for AA with a limit of detection of 0.68 nM and great sensitivity was observed. Importantly, the proposed sensor was evaluated for spiked potato chips samples with a satisfactory result in contrast to high-performance liquid chromatography, confirmed its applicability for the rapid detection of AA.